Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1349-7006.2010.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation‐mediated reduction of LMX1A expression in gastric cancer

Abstract: LMX1A is epigenetically inactivated in cervical cancer. However, the expression and methylation status of LMX1A in gastric cancer tissues remains unknown. In the present study, we found that the expression of LMX1A was significantly decreased in gastric cancer tissues compared with normal tissues. A statistically significant inverse association was found between the LMX1A methylation status and expression of LMX1A in tumor tissues (P = 0.008). Restoration of LMX1A induced cell apoptosis and suppressed anchorag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…8,21 Hypermethylation of LMX1A silences gene expression and induces carcinogenesis. 4 However, overexpression of LMX1A does not affect cell proliferation, but inhibits tumor invasion in cervical cancer. 8 On the contrary, Dong et al 4 demonstrated that silencing LMX1A expression indeed alters gastric cancer cell growth and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,21 Hypermethylation of LMX1A silences gene expression and induces carcinogenesis. 4 However, overexpression of LMX1A does not affect cell proliferation, but inhibits tumor invasion in cervical cancer. 8 On the contrary, Dong et al 4 demonstrated that silencing LMX1A expression indeed alters gastric cancer cell growth and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 Suppression of LMX1A may impair roof plate development in the spinal cord. 5 Hypermethylation can silence LMX1A gene expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our present study represents the first confirmation for the hypermethylation of 8 genes in bladder cancer, although 4 of them were found to be linked with other tumors before. PROX1 and LMX1 are both hypermethylated with expression silence in breast cancer and gastric cancer [39], [40], representing 2 in line with the presumed epigenetical markers in the present panel; whereas the expression of TAL1 was closely associated with T cell acute lymphoblastic leukemia and hypermethylation of SLC6A20 with malignant mesothelioma, but the exact underlying mechnism is to be elucidated yet [41], [42]. The remaining other 4 genes, VAX1 KCNV1, ECEL1 and TMEM26, were found in the present study to be hypermethylated in BC, but there were no any background record that provided mechanisms in the carcinogenesis and development of any cancer, let alone BC.…”
Section: Discussionmentioning
confidence: 99%
“…These unsatisfactory data indicated that it may be necessary to combine other detection methods to improve accuracy. LMX1A methylation is dysregulated in gastric, bladder, breast, ovarian and pancreatic cancer (55)(56)(57)(58). A study on various types of cancer may provide useful insights into the involvement of LMX1A methylation in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%